Penerapan Sistem Personalisasi Akun pada Admisi Online Binus University - Karto Iskandar; Jefriyanto Jefriyanto; Halena Giovanni; Candra Gunawan (ComTech: Computer, Mathematics and Engineering Applications, 2013)
This research purpose is to make easy the registration process of new students by personalizing the account page on admission online. Therefore, each user can manage their own needs and recognize the steps that must be taken to be a BINUS student. Analyses are performed towards the current working system and issues related to the system. Further is performing finding references related to the problem through literature study. Then, creating a UML diagram of the system design, user interface and database. Next is the programming phase and evaluation of the application . The results obtained is an online admission application with a personalized login page. It can be used to make easy the registration of new student or related issue at the many insttutions of Binus. It is suggested to create the mobile version of online admission for the future development.